2020
DOI: 10.1021/acsabm.0c01264
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and One-Step Differentiation of Cross-Reactivity Between Zika and Dengue Virus Using Functional Magnetic Nanosensors

Abstract: Infection with the Zika virus (ZIKV) is an ongoing problem especially as accurate, cost-effective testing remains unresolved. In addition, coinfection occurs with both the Dengue virus (DENV) and ZIKV which leads to cross-reactivity between the flaviviruses and can result in false positives and inaccurate testing. This supports the current need for a simple assay that can detect Zika antibodies sensitively that at the same time can differentiate between cross-reactive antibodies. In this study, we developed cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Appearance of a visible line on the protein A/G test strip indicated that the antibody was successfully conjugated on GNPs (2) and MPnS (3, Figure E). Additionally, we used the spin–spin T2 magnetic relaxation (MR) diagnostic technique, as explained in the previous literature . In brief, binding of target analytes displaced water molecules, leading to measurable changes in the spin–spin magnetic relaxation time (ΔT2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appearance of a visible line on the protein A/G test strip indicated that the antibody was successfully conjugated on GNPs (2) and MPnS (3, Figure E). Additionally, we used the spin–spin T2 magnetic relaxation (MR) diagnostic technique, as explained in the previous literature . In brief, binding of target analytes displaced water molecules, leading to measurable changes in the spin–spin magnetic relaxation time (ΔT2).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we used the spin−spin T2 magnetic relaxation (MR) diagnostic technique, as explained in the previous literature. 59 In brief, binding of target analytes displaced water molecules, leading to measurable changes in the spin−spin magnetic relaxation time (ΔT2). This was observed with the MPnS measured at 102 ms and the MPnS-Ab increasing to 115 ms (Figure 2F).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…However, these specific antibody/antigen-based assays show poor sensitivity in the first few days of infection, particularly during the acute phase. Clinical statistics show that anti-CHIKV lgM is only detectable from day 4 to day 7 of sickness, resulting in false-negative results [6]. Due to their higher sensitivity and specificity, molecular diagnostic techniques can detect viruses early in infection within the window period of pathogen-specific antibody/antigen detection [7].…”
Section: Introductionmentioning
confidence: 99%